The study of supercritical extraction of complexes of molybdenum with carbon dioxide - Borts, Boris; Skoromnaya, Stella; Palamarchuk, Anna; Tkachenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2016)
Characteristics of short-living isotope 99mTc, the main instrument of nuclear medicine derived as a result of radioactive isotope 99Mo decay was given. 85 % of all diagnostics scans in the world for treatment of cancer diseases are conducted using the 99mTc isotope. In order to solve the problem of 99Mo isotopes extraction probe preparation and extraction method for Mo included in nitrate-containing complexes with tributyl phosphate (TBP) from molybdenum containing matrixes by the method of supercritical extraction with carbon dioxide (SCE-CO2) were offered. Quasi-periodic dependence of residual content of Mo in nitric acid solution on dilution time was shown, for the description of which the three-trophic model was offered. Theory of description of Mo dissolution in the diluted nitric acid by means of channels and jokers method was offered which gives good correspondence with experimental data. The content of Mo as a SCE-CO2 extraction under different variations of modifiers and ways of extraction was studied. It was shown that the largest efficiency of Mo extraction reaches 90 % and is observed under the following ratio of modifiers: 0.2 ml TBP+Mo, 0.1 ml of acetyl-acetone and 0.05 ml of water.